Stability of Uniformly Attracting Sets for Impulsive-Perturbed Multi-Valued Semiflows. Issue 2 (2020) - Dashkovskiy, Sergey; Kapustyan, Oleksiy; Perestyuk, Yuriy
Abstract: In this paper we investigate stability of uniformly attracting sets for semiflows generated by impulsive infinite-dimensional dynamical systems without uniqueness. Obtained abstract results are applied to weakly nonlinear parabolic system, whose trajectories have jumps at moments of intersection with certain surface in the phase space.